2019
DOI: 10.1016/j.scitotenv.2018.09.247
|View full text |Cite
|
Sign up to set email alerts
|

Dioxin and AHR impairs mesoderm gene expression and cardiac differentiation in human embryonic stem cells

Abstract: Dioxin and dioxin-related polychlorinated biphenyls are potent toxicants with association with developmental heart defects and congenital heart diseases. However, the underlying mechanism of their developmental toxicity is not fully understood. Further, different animals show distinct susceptibility and phenotypes after exposure, suggesting possible species-specific effects. Using a human embryonic stem cell (ESC) cardiomyocyte differentiation model, we examined the impact, susceptible window, and dosage of 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Furthermore, the prototypical environmental AhR ligand, 3,4,7,8-tetrachlorodibenzo- p -dioxin (TCDD) has been reported to induce cardiomyopathies, cardiac lesions, arteritis, and atherosclerosis in rodents, and increase the risk of CVD in humans [83]. Recently it was also shown that TCDD inhibits cardiomyocyte differentiation from human embryonic stem cells via AhR-regulated mechanisms [90].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the prototypical environmental AhR ligand, 3,4,7,8-tetrachlorodibenzo- p -dioxin (TCDD) has been reported to induce cardiomyopathies, cardiac lesions, arteritis, and atherosclerosis in rodents, and increase the risk of CVD in humans [83]. Recently it was also shown that TCDD inhibits cardiomyocyte differentiation from human embryonic stem cells via AhR-regulated mechanisms [90].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence shows that AHR plays a central role in the development and function of the cardiovascular system in fish, mice, and humans. Many studies have demonstrated that the activation of AHR could lead to the generation of reactive oxygen species (ROS) through the upregulation of cytochrome P450 enzymes (CYPs). , In the current study, an induced oxidative stress response, combined with an up-regulation of cyp1a1 mRNA expression specifically, suggests there is an AHR-mediated induction of ROS following PFOSA exposure. During early life stages of development, the heart is particularly sensitive to ROS-induced oxidative stress, with an excessive amount of ROS production capable of causing heart failure .…”
Section: Discussionmentioning
confidence: 59%
“…The AhR plays a critical role in cardiac development and function (Chen et al, 2022; Fu et al, 2019). Flumioxazin exposure induced significant up‐regulation of AhR pathway‐related genes ( ahr2, cyp1a1 , and cyp1b1 ).…”
Section: Discussionmentioning
confidence: 99%